CO2 tax scenarios for Austria: Impacts on household income groups, CO2 emissions, and the economy - Mathias Kirchner; Mark Sommer; Claudia Kettner-Marx; Daniela Kletzan-Slamanig; Katharina Köberl; Kurt Kratena (Austrian Institute of Economic Research (WIFO), 2018)
We assess distributive, macroeconomic, and CO2 emission impacts of CO2 tax schemes in Austria by applying the macroeconomic Input-Output model DYNK[AUT]. The tax schemes analysed focus primarily on CO2 emissions not covered by the European Emission Trading System (ETS), applying different CO2 tax rates as well as tax compensation schemes. We perform comparative scenario analysis for our model's base year (i.e., short-term impacts). Our model simulations indicate that - without tax compensation - impacts on households can be regressive if measured as tax burden relative to income, and are found to be rather proportional if measured as tax burden relative to expenditure or as changes in total expenditure and income. Lower income households benefit more from tax compensations (lump sum payments), i.e., CO2 taxes with compensation measures for households lead to progressive tax burden impacts. Energy-related CO2 emissions decrease quite substantially in non-ETS sectors, although households react inelastic. Value added in most non-ETS industry and service sectors declines only slightly without tax compensation and commodity import shares are hardly affected. Decreasing employers' social contribution (i.e., lowering labour costs) mitigates negative impacts in most non-ETS industry and service sectors. GDP decreases very moderately without tax recycling, depending on the tax rate. Employment effects are similar but smaller. Tax recycling leads to negligible GDP impacts and increases employment. Our simulations thus suggest that CO2 taxes could be a crucial and socially acceptable element within a comprehensive set of policy instruments in order to contribute to achieving greenhouse- gas emission targets for non-ETS sectors in Austria.
Keywords: C22; C63; C67; E12; E61; H23; 330; climate change; CO2 taxes; distributive impacts; macroeconomic modeling